Dampak Media Sosial terhadap Perilaku Keagamaan pada Masyarakat di Desa Tanjung Medan Kabupaten Labuhanbatu - Wirman, Wirman; Zulkarnaen, Zulkarnaen; Rambe, Aminah (AHKAM, 2024)
This research aims to investigate the impact of social media on religious behavior in the community of Tanjung Medan Village, Labuhanbatu Regency. Social media has become an integral part of everyday life, influencing various aspects including religion. Tanjung Medan Village was chosen as the research location because it has characteristics of a community that is still strong in traditional religious values. The research method used is field research with a qualitative approach. Data was collected through in-depth interviews, observation and analysis of social media content. Respondents consisted of various age groups and religious backgrounds to gain a comprehensive understanding. The research results show that social media has a significant impact on religious behavior in Tanjung Medan Village. Openness of information through social media accelerates the spread of religious values, but can also trigger changes in attitudes and interpretations of religion. Social media also facilitates interaction between individuals with diverse religious understandings, producing new dynamics in society's religious practices. Although social media provides widespread access to religious information, this research also identifies challenges, such as the spread of false information or religious radicalism. Therefore, efforts are needed to increase media literacy and people's religious understanding in dealing with the impact of social media.